2015
DOI: 10.1371/journal.pone.0117709
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Regeneration of Completely Transected Spinal Cord Using Induced Neural Stem Cells and Gelatin-Electrospun Poly (Lactide-Co-Glycolide)/Polyethylene Glycol Scaffolds

Abstract: Tissue engineering has brought new possibilities for the treatment of spinal cord injury. Two important components for tissue engineering of the spinal cord include a suitable cell source and scaffold. In our study, we investigated induced mouse embryonic fibroblasts (MEFs) directly reprogrammed into neural stem cells (iNSCs), as a cell source. Three-dimensional (3D) electrospun poly (lactide-co-glycolide)/polyethylene glycol (PLGA-PEG) nanofiber scaffolds were used for iNSCs adhesion and growth. Cell growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 42 publications
(61 reference statements)
0
69
0
1
Order By: Relevance
“…As one of the few biomaterials approved by the United States Food and Drug Administration (FDA) and European Medicine Agency (EMA) for experimental and clinical application, PLGA has broad utility in drug delivery, artificial catheter and tissue engineering67. Due to the easy controlling of mechanical properties and biodegradation, PLGA is one of the top biodegradable synthetic polymers used for tissue engineering, especially neural tissue engineering8. It has been used as carrier for various cells to restore injured nerve910.…”
mentioning
confidence: 99%
“…As one of the few biomaterials approved by the United States Food and Drug Administration (FDA) and European Medicine Agency (EMA) for experimental and clinical application, PLGA has broad utility in drug delivery, artificial catheter and tissue engineering67. Due to the easy controlling of mechanical properties and biodegradation, PLGA is one of the top biodegradable synthetic polymers used for tissue engineering, especially neural tissue engineering8. It has been used as carrier for various cells to restore injured nerve910.…”
mentioning
confidence: 99%
“…A number of studies focused on the capability of biomaterial scaffolds seeded with differentiated stem cells to treat SCI (Agbay et al, ; Libro et al, ; Liu et al, ; Shrestha et al, ; Tabesh et al, ; Xia et al, ; Yang et al, ), and here we present a novel combination of PCL/gelatin scaffolds seeded with hEnSCs that have been differentiated by coculturing with hSCs to treat SCI in rats. This study is significant for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, owing to their well-controlled degradation rate, low toxicity as well as immunogenicity [8], PLGA complexes seem to be an expedient complex for the adherence and growth of inoculating cells. Similarly, a number of studies have postulated OECs to be a suitable choice for the treatment and replacement of injured spinal cord by virtue of their multi-lineage differentiation potential coupled to a unique self-renewal ability [23, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several investigations into engineered bio-constructs that use various types of cell-seeded bio-complexes [5-7], the two integral parts being an appropriate cell source and a suitable complex [8]. A number of previous studies have shown that transplantation of neural stem cells like embryonic stem cells [9], mesenchymal stem cells [10] and glial cells, such as schwann cells [11], bone marrow stromal cells [12]or olfactory ensheathing cells [13] into the lesion site of the SCI can significantly promote axonal regeneration and functional recovery.…”
Section: Introductionmentioning
confidence: 99%